Real time actions and gestures as intuitive user interface for creative 3D modeling - Looi, N.K.; Loo, C.K.; Pau, K.N. (2005)
Current 3D modeling systems do not support the importance of creativity on design process during the conceptual phase effectively. In other words, there are no toolls, which support the creative 3D modeling of a virtual visual design in the preliminary phase, where different variations have to be discussed. Therefore an intuitive UI for 3D modeling applications that supports creative concept development would be helpful to increase productivity and creativity. Rather than depend on default interaction techniques, which occupy and shape us for decades, it is critical that we should explore alternative interaction methods that are well suited with the new media intuitively. In this paper an innovative UI concept is presented by integrating new generation of input devices such as data glove and 3D motion sensor. An immersive visual design system with the combination of real time actions and gestures are applied to support natural interaction.